2019
DOI: 10.1051/meca/2019030
|View full text |Cite
|
Sign up to set email alerts
|

Bending improvement in Spot Heating of pipes in comparison with Line Heating method

Abstract: In Spot Heating, a small area of a metal part surface is heated quickly with a gas torch, laser beam, or induction coil to a temperature below the phase change temperature and then cools down. The heated area undergoes compressive plastic strain and the part gets deformed. This method is usually applied as trial and error for straightening shafts, bridge components, ship structures, etc. The conventional straightening mechanism in industries involves creating thermal gradient mechanism (TGM) and shortening. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Ferreño et al [26] have demonstrated that the end results of the flaming of a steel beam can be predicted using finite element analysis. Chavoshi et al [27] have demonstrated that the end results of the hot spotting of a hollow shaft can be predicted using finite element analysis. Hu et al [28] have shown that the effect of laser peening on the geometry and residual stresses of specimens can be predicted.…”
Section: Discussionmentioning
confidence: 99%
“…Ferreño et al [26] have demonstrated that the end results of the flaming of a steel beam can be predicted using finite element analysis. Chavoshi et al [27] have demonstrated that the end results of the hot spotting of a hollow shaft can be predicted using finite element analysis. Hu et al [28] have shown that the effect of laser peening on the geometry and residual stresses of specimens can be predicted.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous researches [1,8], the spot heating of a pipe was optimized using the Gaussian heat distribution of the torch to increase bending. The parametric study showed that increasing the heating zone radius and the maximum heat intensity, first, led to an increase in pipe bending angle and then a decrease.…”
Section: Heat Flux Distributionmentioning
confidence: 99%
“…The heated zone expands and is subjected to the pressure of the surrounding cold zone. Increasing the temperature leads to an increase in compressive stress and a reduction in the yield stress of the heated zone, a slight bulging, plastic strain, and ultimately reducing the length of the heated zone after cooling and deformation of the piece [1,2]. Li and Yao [3] examined various mechanisms of thin pipe deformation by heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation